2018
DOI: 10.1111/1759-7714.12885
|View full text |Cite
|
Sign up to set email alerts
|

Value of the preoperative neutrophil‐to‐lymphocyte ratio as a prognostic factor for long‐term survival in postoperative esophageal squamous cell carcinoma patients

Abstract: BackgroundThis study investigated the relationship between the neutrophil‐to‐lymphocyte ratio (NLR) and clinicopathological features and prognosis in patients with postoperative esophageal squamous cell carcinoma (ESCC).MethodsThe preoperative NLR was evaluated in 419 patients who underwent esophagectomy for ESCC. A receiver operating characteristic (ROC) curve was plotted to verify the accuracy of the NLR for predicting survival. Correlation between the NLR and clinicopathological characteristics was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Besides, the locoregional relapse rate was significantly higher in the patients with NLR ≥2.8. Similar to the findings observed in other studies, we showed that high pre-operative NLR negatively affected both DFS and OS [ 12 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, the locoregional relapse rate was significantly higher in the patients with NLR ≥2.8. Similar to the findings observed in other studies, we showed that high pre-operative NLR negatively affected both DFS and OS [ 12 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Duan et al [ 14 ] found that patients with high pre-operative NLR had significantly worse tumor-specific survival and recurrence-free survival rates than those with low pre-operative NLR in ESCC patients who underwent curative surgery, indicating that NLR had the most significant predictive effect, particularly for patients with Stage IIIA disease. Similarly, Xu et al [ 15 ] reported the cutoff value for NLR to be 2.99 in their study with ESCC patients and concluded that pre-operative NLR was significantly associated with long-term prognosis, especially in patients with lymph node metastasis and Stage II–III disease. However, Rashid et al [ 16 ] reported that NLR (cutoff; 3.5) was not associated with DFS in their study including 294 EC patients, only 50 of whom were ESCC.…”
Section: Discussionmentioning
confidence: 91%
“…The close link between inflammation and cancer is well documented, and many reports have shown a correlation between prognosis and systemic inflammation. 7 Among the blood parameters thought to reflect systemic inflammation (eg, C-reactive protein), evidence suggests the preoperative NLR associates with survival in several solid tumors. 8 Moreover, some reports suggest a relationship between the NLR and lymph node metastasis in various cancers, including advanced gastric cancer and esophageal squamous cell cancer.…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, some reports suggest a relationship between the NLR and lymph node metastasis in various cancers, including advanced gastric cancer and esophageal squamous cell cancer. 7,9 Patients with lymph node metastasis and a high blood NLR had significantly poorer cancer-specific survival than those with a low NLR. 7 The present study suggests there is no significant association between the NLR and CD16b-positive neutrophil accumulation or lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation